The Process of Wedding Ceremony in Tulehu Village, Central Moluccas (A Historical Analysis) - Rosmiaty Rosmiaty; Abdollah Abdollah; Rahmuni Lestaluhu (Fakultas Sastra - Universitas Muslim Indonesia, 2016)
This study aims (1) to find out about The Process of wedding Ceremony in Tulehu village Central Moluccas (2) to determine the values are ​​contained in The Process of Wedding Ceremony in Tulehu village, Central Moluccas. This study used descriptive qualitative method to analysis the process of wedding ceremony in Tulehu village, central Moluccas. The results of this study include of the process of wedding ceremony in Tulehu village, central Moluccas. There are informal notification, login request, event nahusanamng and sitting gifts, delivery of property / fare and marriage ceremony. In addition, the values ​​contained in the customary marriage of Tulehu village, district. such as moral values, social values ​​and religious values. The results of this study are also expected to religious leaders and community leaders in Tulehu village, Central Maluku district. to teach the customary marriage procedure to the young generation. So that culture is also known by the younger generation. in order to be inherited later. Thus, the values ​​contained in the customary marriage process are not lost.